Sustainable residential interiors - Foster, Kari (John Wiley & Sons, 2007)
Sustainable Residential Interiors takes readers through an integrated design process, showing how sustainable principles and practices can be applied on virtually every level of interior design. Taking a practical, hands-on approach, this accessible and easy-to-understand resource guide includes: Visual examples of sustainable projects and applications; Critical thinking about environmental issues within homes; Guidelines for clients and project teams; Helpful checklists for greening projects and specification; In-depth information to promote understanding and assist in specifying interior finishes and furnishings; Questions for manufacturers and vendors; Effective methods of marketing sustainable design services.